2022
DOI: 10.3390/ijms23147665
|View full text |Cite
|
Sign up to set email alerts
|

The Puzzle of Hereditary Spastic Paraplegia: From Epidemiology to Treatment

Abstract: Inherited neurodegenerative pathology characterized by lower muscle tone and increasing spasticity in the lower limbs is termed hereditary spastic paraplegia (HSP). HSP is associated with changes in about 80 genes and their products involved in various biochemical pathways, such as lipid droplet formation, endoplasmic reticulum shaping, axon transport, endosome trafficking, and mitochondrial function. With the inheritance patterns of autosomal dominant, autosomal recessive, X-linked recessive, and mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 72 publications
0
20
0
1
Order By: Relevance
“…In the current study, we identified two novel SPG 11 gene mutations: a frameshift (c.5687_5691del) and a non-sense mutation (c.751C>T). SPG11-associated HSP is supposed to be the most frequent type of complicated autosomal recessive HSP, especially for patients with a thin corpus callosum and intelligence disorder (Paisanruiz et al, 2008;Meyyazhagan et al, 2022). The SPG 11 gene, which is located at chromosome 15q13-15, encodes the spatacsin protein that is primarily expressed in the pineal gland, cerebral cortex, cerebellum, and hippocampus (Paisanruiz et al, 2008;Samaranch et al, 2008;Panza et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we identified two novel SPG 11 gene mutations: a frameshift (c.5687_5691del) and a non-sense mutation (c.751C>T). SPG11-associated HSP is supposed to be the most frequent type of complicated autosomal recessive HSP, especially for patients with a thin corpus callosum and intelligence disorder (Paisanruiz et al, 2008;Meyyazhagan et al, 2022). The SPG 11 gene, which is located at chromosome 15q13-15, encodes the spatacsin protein that is primarily expressed in the pineal gland, cerebral cortex, cerebellum, and hippocampus (Paisanruiz et al, 2008;Samaranch et al, 2008;Panza et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 3). The diagnosis of autosomal recessive HSP with a thin corpus callosum was finally confirmed according to the clinical manifestations and genetic test results of the patient (Patel et al, 2016;Zhang et al, 2016;Meyyazhagan et al, 2022). The Spastic Paraplegia Rating Scale (SPRS) was 16 points according to a previous study (Schüle et al, 2006).…”
mentioning
confidence: 99%
“…Hereditary spastic paraplegias (HSPs) are a diverse group of heritable neurological disorders, which are clinically characterized by spastic and weakness in lower-extremities, and pathologically by retrograde axonal degeneration. To date, no etiological treatments for prevention or reversal of motor neuron degeneration in HSP have been documented [9] . Symptomatic treatments via physical or occupational therapy and drugs have improved muscle spasticity only temporarily and improved balance, strength, and agility.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, HSPs are classified as pure or complex based on the presence of any other neurological manifestations besides paraparesis, such as seizures, dementia, intellectual disability, peripheral neuropathy, or developmental delay (Lallemant‐Dudek & Durr, 2021). A spastic paraplegia gene (SPG) designation is used to classify HSP based on genetic sequencing of the chromosomal loci or genes, and over 80 SPG genes have been identified to date (Meyyazhagan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%